Diversity of Butterflies in The Papilionoidea Superfamily (Lepidoptera) in Residential Areas Of Jambi City - Bayu Kurniawan; Nisma Hariyanti Ritonga (DIVERSITAS HAYATI, 2023)
Butterflies are species with various benefits at each level of ecological niches, including their role as environmental quality bioindicators. The presence of human settlements poses a challenge to maintaining the sustainability of various species, including butterflies. This research aims to determine the diversity and dominance of butterfly species in residential areas in Amuntai, Kota Jambi. Data collection was conducted using an exploratory method by exploring the research location once a week in the morning for two months. In this study, 8 butterfly species were found from 2 families, namely Pieridae consisting of 3 species (Leptosia nina, Eurema hecabe, Appias libythea) and Nymphalidae consisting of 5 species (Neptis hylas, Elymbias nesaea, Junonia hedonia, Junonia orithya, Junonia atlites) with H' value of 1.97 and D value of 0.15.